Increasing Communication Effectiveness and Efficiency between the Department of Agriculture and The Cypriot Farmers They serve - Eftychia Charalambous-Snow; Patreese Ingram (Journal of International Agricultural and Extension Education, 2011)
An exploratory research study was conducted to determine the current practices of communicating information between officers of the Cypriot Department of Agriculture and farmers in Cyprus in an attempt to improve its effectiveness and efficiency and thereby strengthen the Extension Service of the Department of Agriculture. The variables studied were type and content of information, method of communication, and training received during 2009. The study used a descriptive survey research methodology, organized into three phases with two interview schedules developed to collect the data from a stratified random sample of 225 Cypriot farmers. A total of 124 farmers were interviewed, resulting in a 55% response rate. When the communication methods were analyzed, the farmers indicated a preference for receiving written materials while visits from officers were also popular. The farming television program was preferred to its radio equivalent while electronic communication methods were favored only by few farmers, mainly the larger commercial farms. A large number of the farmers indicated that they received very limited information or training from the Department of Agriculture during 2009 with some relying on information and training from other sources. Given these findings, it is recommended that a communication strategy be developed so that the Department of Agriculture will become more apparent and relevant to the farmers it serves.
Keywords: Agricultural extension; communication methods; communication efficiency; Cypriot farmers; Cyprus Department of Agriculture